Fake Profile Detection on Social-Media - Shamim Ahmad; Dr. Manish Madhava Tripathi (International Journal of Engineering and Management Research, 2023)
In this generation, social media platforms such as Twitter, Instagram, Linkedln, and others play an important role in our everyday lives. The whole world is actively involved. However, it must also address the problem of false profiles. The majority of fake pattern are generated by human or robots or cyborgs built to spread for misinformation, data piracy and identity theft. Therefore, In this article, we will discuss a model name as Detection of fake profile on social media model, which will be differentiate between fake and real profile on twitter based on visible features like, friend counts, follower counts, status counts, and more by using various machine learning classification methods. The dataset will be used twitter profile and we will Taking the Machine learning classification model like, Neural Network (NN), Random Forest, XG-Boost, and LSTM for determining the authenticity of a social media profile and for used implementation language is Python3 along with all the required libraries like, pandas, NumPy, and Sklearn etc.